ULTCC-Compatible LiPO3Ceramic with Ultralow Permittivity for 5G High-Gain Antenna Array Applications - Bao, Jian; Guo, Jing; Zhou, Tao; Jiang, Jia Pei; Du, Chao; Wang, Xin; Xi, Zhao Chen; Pang, Li Xia; Tan, Kar Ban; Zhou, Di (American Chemical Society, 2026)
In contemporary radio frequency (RF) systems, organic substrate materials are extensively utilized due to their low permittivity. However, their low thermal conductivity (κ ≈ 0.25 W/(m·K)) can lead to catastrophic thermal management issues in RF systems. This work proposes a LiPO3 ceramic substrate, which demonstrates ultralow permittivity (εr ≈ 4) and exceptional quality factors (tanδ at the 10–4 level). However, the temperature coefficient of resonant frequency for the LiPO3 ceramic is a large negative value (TCF ≈ −110 ppm/°C), which requires further adjustment. The εr of LiPO3 is comparable to that of organic laminates, which helps reduce signal delay, and its high quality factor gives it excellent frequency selectivity. The low ionic polarizability of Li+ and P5+ in combination with the unique (PO3)n chain structure of the phosphate groups in LiPO3 is intrinsically responsible for its low permittivity. In addition, the κ of LiPO3 exceeding 2 W/(m·K) contributes to extending the lifespan of the RF components. Furthermore, LiPO3 has a sintering temperature of only 630 °C and does not undergo chemical reactions or physical penetration with aluminum. This suggests its potential in the ultralow temperature cofired ceramics (ULTCC) field. The potential of LiPO3 was validated through an antenna array application in the 5G network. This work effectively resolves the conflict between signal delay and thermal management in high-integration RF systems.